COST OF ACTIVITIES IN PUBLIC UTILITY FLEETS - Manojlović, Aleksandar; Medar, Olivera; Trifunović, Jelena; Vukadinović, Katarina (Journal of Applied Engineering Science, 2012)
With each day more present tendencies in business systems to focus on core processes, the position of the transport activity and the vehicle fleet within is imperatively examined: is it an activity creating an added value to the core system or a mere unavoidable cost-maker. A decisive role is attributed to the manner of defining the vehicle utilisation and the way of realisation of fleet related activities. Therefore, a link between activity based costing and the transport department (subsystem) has been presented in this paper. This link is especially important in public utility fleets. In the paper are presented the fleet activities and a proposal for cost allocation method in the fleet. As large fleets represent an integral part of the public utility systems, changes in business conditions at the present time will cause a need for improvement in fleet cost allocation, and therefore activity based costing. Will this engender the need for the creation of city fleets?